Systematic Literature Review: The Influence of Management Accounting Information Systems on Organizational Performance - Mery Rohaya Sihombing; Wirmie Eka Putra; Yuliusman; Fredy Olimsar (Syntax Corporation, 2026)
The rapid advancement of information technology has made Management Accounting Information Systems (MAIS) essential for supporting managerial decision-making and improving organizational efficiency, yet the extent of their influence on organizational performance remains fragmented in the literature. This research aims to analyze and map the development of literature regarding the influence of Management Accounting Information Systems (MAIS) on organizational performance. The study applies a Systematic Literature Review (SLR) approach following PRISMA guidelines. Articles were identified from Scopus, Google Scholar, Emerald, and ScienceDirect databases from 2023–2025. Initial identification found 152 articles, and after screening, 25 articles met inclusion criteria. Findings indicate that MAIS positively influences organizational performance through improved decision-making quality, operational efficiency, managerial control, and strategic alignment. However, organizational culture, technological readiness, and top management support remain important moderating factors. In conclusion, the mere implementation of MAIS is insufficient; rather, its effectiveness depends on contextual alignment and organizational capabilities, and future research should explore mediating variables and emerging technologies such as artificial intelligence and cloud-based systems.